Homesteading Kontemporer sebagai Strategi Pengabdian kepada Masyarakat Berbasis Keberlanjutan - Meistian Herizon; Didi Ardiansyah; Radeni Ilyan Putra; Reflis, Reflis; Satria P. Utama (Yayasan Literasi Sains Indonesia, 2025)
This study explores the contemporary homesteading lifestyle, which is gaining increasing attention as part of a movement toward community self-reliance and sustainability. The contemporary homesteading emphasizes self-sufficient food production, efficient resource management, and the application of sustainable living practices across various spatial contexts, from rural areas to densely populated urban environments. Using a qualitative literature review approach, this article analyzes the key characteristics, benefits, implementation challenges, and potential applications of homesteading in community service activities (PkM). The findings indicate that homesteading contributes to household economic resilience, physical and mental health, environmental conservation, and the strengthening of social networks. However, this practice also faces obstacles such as limited land availability, lack of technical skills, regulatory constraints, and social resistance. In the Indonesian context, it is becoming increasingly relevant in line with the growth of urban agriculture and the need for community-based solutions. This article offers a thematic framework that can serve as a foundation for developing PkM programs based on sustainable lifestyles adapted to regional diversity. This study is expected to make a significant contribution to strengthening the connection between academic literature and household-based community empowerment practices.